Sex Differences in Sleep Architecture After Traumatic Brain Injury: Potential Implications on Short-Term Episodic Memory and Recovery - Stefanie N. Howell; Grace S. Griesbach (Neurotrauma Reports, 2024)
Sleep-wake disturbances (SWDs) are common after TBI and often extend into the chronic phase of recovery. Such disturbances in sleep can lead to deficits in executive functioning, attention, and memory consolidation, which may ultimately impact the recovery process. We examined whether SWDs post-TBI were associated with morbidity during the post-acute period. Particular attention was placed on the impact of sleep architecture on learning and memory. Because women are more likely to report SWDs, we examined sex as a biological variable. We also examined subjective quality of life, depression, and disability levels. Data were retrospectively analyzed for 57 TBI patients who underwent an overnight polysomnography. Medical records were reviewed to determine cognitive and functional status during the period of the sleep evaluation. Consideration was given to medications, owing to the fact that a high number of these are likely to have secondary influences on sleep characteristics. Women showed higher levels of disability and reported more depression and lower quality of life. A sex-dependent disruption in sleep architecture was observed, with women having lower percent time in REM sleep. An association between percent time in REM and better episodic memory scores was found. Melatonin utilization had a positive impact on REM duration. Improvements in understanding the impact of sleep-wake disturbances on post-TBI outcome will aid in defining targeted interventions for this population. Findings from this study support the hypothesis that decreases in REM sleep may contribute to chronic disability and underlie the importance of considering sex differences when addressing sleep.